Dampak Perilaku Konsumen Terhadap Niat Pembelian Polis Allianz dengan Moderator Kepercayaan Merek - Novandi Santoso; Richard Andrew (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to analyze the impact of behavior on the purchase intention of Allianz insurance policies in Bengkulu City and to examine the moderating role of brand trust. The low interest in purchasing insurance policies is influenced by consumer distrust, negative stigma, and past unsatisfactory experiences. In the digital marketing era and increasing competition within the insurance industry, psychological aspects such as consumer attitude and trust play a crucial role in determining purchase intention. This research employed a quantitative method with a causal approach and a cross-sectional survey design. Data were collected through an online questionnaire distributed to 90 respondents, consisting of active Allianz policyholders in Bengkulu City selected using purposive sampling. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings show that behavior has a positive and significant effect on purchase intention (p-value 0.000; t=3.613). Brand trust also has a positive and significant effect on purchase intention (p-value 0.002; t=3.047). Moreover, brand trust significantly moderates the effect of behavior on purchase intention (p-value 0.037; t=2.091). These results highlight the importance of strengthening brand trust strategies to enhance insurance policy purchase intentions in the digital era.